Assessment of acetylcholinesterase activity using indoxylacetate and comparison with the standard Ellman's method - Pohanka, Miroslav; Hrabinova, Martina; Kuca, Kamil; Simonato, Jean-Pierre (International journal of molecular sciences, 2011)
Assay of acetylcholinesterase (AChE) activity plays an important role in diagnostic, detection of pesticides and nerve agents, in vitro characterization of toxins and drugs including potential treatments for Alzheimer's disease. These experiments were done in order to determine whether indoxylacetate could be an adequate chromogenic reactant for AChE assay evaluation. Moreover, the results were compared to the standard Ellman's method. We calculated Michaelis constant Km (2.06 × 10(-4) mol/L for acetylthiocholine and 3.21 × 10(-3) mol/L for indoxylacetate) maximum reaction velocity V(max) (4.97 × 10(-7) kat for acetylcholine and 7.71 × 10(-8) kat for indoxylacetate) for electric eel AChE. In a second part, inhibition values were plotted for paraoxon, and reactivation efficacy was measured for some standard oxime reactivators: obidoxime, pralidoxime (2-PAM) and HI-6. Though indoxylacetate is split with lower turnover rate, this compound appears as a very attractive reactant since it does not show any chemical reactivity with oxime antidots and thiol used for the Ellman's method. Thus it can be advantageously used for accurate measurement of AChE activity. Suitability of assay for butyrylcholinesterase activity assessment is also discussed.
Keywords: pyridinové sloučeniny; oximy; Enzyme Assays; indoly; nerve agents; Indoles; Substrate Specificity; Pyridinium Compounds; paraoxon; Pralidoxime Compounds; Oximes; Paraoxon; indoxylacetate; enzymatické testy; acetylcholinesterase; enzyme activity; Alzheimer’s disease; cholinesterasové inhibitory; Kinetics; kinetika; substrátová specifita; Acetylcholinesterase; oxime reactivator; 5,5′-dithio-bis-2-nitrobenzoic acid; reaktivátory cholinesterasy; Cholinesterase Reactivators; Dithionitrobenzoic Acid; Obidoxime Chloride; pralidoximové sloučeniny; kyselina dithionitrobenzoová; obidoxim chlorid; acetylcholinesterasa; Cholinesterase Inhibitors